2010
DOI: 10.1038/ng.527
|View full text |Cite
|
Sign up to set email alerts
|

Identification of DOK genes as lung tumor suppressors

Abstract: Genome-wide analyses in human lung adenocarcinoma have identified regions of consistent copy number gain or loss, but in many cases the oncogenes and tumor suppressors presumed to reside in these loci remain to be determined. Here we identify the "Downstream of tyrosine kinase" (Dok) family members Dok1, Dok2 and Dok3 as lung tumor suppressors. Single, double, or triple compound loss of these genes in the mouse results in lung cancer with penetrance and latency dependent on the number of lost Dok alleles, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
133
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(138 citation statements)
references
References 38 publications
4
133
1
Order By: Relevance
“…The incidence of macrophage accumulation in the lung was intermediate (3 of 8) in age-matched Dok-3 À/À mice. Although development of lung adenocarcinoma, but not aggressive HS, has recently been reported in mice lacking Dok-1, Dok-2, and/or Dok-3 on a pure 129S1/SvImj genetic background even at the age of 11-15 months, 23 in this study mice mu- tated in the same genes, but on a 129/SvJ and C57BL/6 mixed background, did not exhibit elevated incidence of lung adenocarcinoma. These different findings are likely due to the difference in the genetic backgrounds.…”
Section: Tko Mice Show Abnormal Accumulation Of Macrophages In the Lungcontrasting
confidence: 62%
“…The incidence of macrophage accumulation in the lung was intermediate (3 of 8) in age-matched Dok-3 À/À mice. Although development of lung adenocarcinoma, but not aggressive HS, has recently been reported in mice lacking Dok-1, Dok-2, and/or Dok-3 on a pure 129S1/SvImj genetic background even at the age of 11-15 months, 23 in this study mice mu- tated in the same genes, but on a 129/SvJ and C57BL/6 mixed background, did not exhibit elevated incidence of lung adenocarcinoma. These different findings are likely due to the difference in the genetic backgrounds.…”
Section: Tko Mice Show Abnormal Accumulation Of Macrophages In the Lungcontrasting
confidence: 62%
“…Dok-1, Dok-2, and Dok-3 constitute a closely related subfamily of the Dok adaptor proteins, which emerged as negative regulators of PTK-induced signaling and cellular transformation driven by OTKs (15,21,63,67,80,95). Findings that their loss promotes transformation or disease progression initiated by deregulated PTKs (4,21,54,63,67,95) suggest that their inactivation could constitute an important component of OTK-driven malignant transformation. However, mechanisms by which OTKs could regulate Dok proteins remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, more recent studies have shown that mice with combined Dok-1, Dok-2, and Dok-3 knockouts also succumb to aggressive histiocytic sarcoma (54) or develop lung adenocarcinoma with penetrance and latency dependent on the number of lost Dok family members (4). Finally, DOK-2 has been reported to be a target of frequent copy number loss in human lung cancer (4).…”
mentioning
confidence: 99%
“…Although DLC1 is at an epicenter of deletions, these deletions are frequently much larger and reduce the dosages of tens or hundreds of genes, often encompassing the entire 8p22 cytoband and beyond (2,5,6). Indeed, multiple candidate TSGs have been proposed in the region (5)(6)(7)(8). Here we explore the hypothesis that chromosome 8p deletions arise owing to selection for the attenuation of multiple genes.…”
mentioning
confidence: 99%